Pengembangan Karakter Peserta Didik Melalui Pendidikan Nilai: Pendekatan Psikologi Pendidikan Dalam Membentuk Akhlak Sopan Santun Kepada Guru - Kiki Mohammad Iqbal; Akhmad Fauzi (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2026)
This study critically examines the fragmentation between Islamic transcendental ethics and Western educational psychology frameworks in addressing student moral decline, particularly concerning the ethics of respect for teachers. Educational institution monitoring data from 2021–2025 confirms a structural increase in incidents of verbal and physical disrespect, reflecting weak internalization of spiritual values, pedagogical inconsistency, and the digital normalization of discourteous behavior. Although recent literature has extensively discussed values education, social learning theory, and ethics of care in isolation, a substantive gap remains: the absence of an operational model that simultaneously integrates spiritual motivation, cognitive-moral development, care relationships, and digital-ecological pressures. This paper addresses this gap through the development of the Model for Integrating Adab, Role Modeling, and Ethics of Care (MIAKEK), employing a comparative-integrative qualitative design. The model synthesizes classical Islamic pedagogy with contemporary educational psychology into a coherent, multidimensional framework. The findings affirm that respect for teachers functions as both a transcendental obligation and a psychological need, necessitating integrated interventions in spiritual internalization, consistent educator role modeling, alignment of the hidden curriculum, and collaboration among the three pillars of education. The novelty of this study lies in its explicit theoretical bridge, mapping of operational indicators, and a policy architecture ready for empirical validation. Keywords: Values Education, Ethics of Respect for Teachers, Character Development, Educational Psychology